(untitled) (Al-Academy, 2025)
The research is interested in studying the sensory stimulus and its role in understanding and interpreting the contemporary industrial product. The research problem was defined by the following question: What is the nature of the sensory stimulus and its role in understanding and interpreting the contemporary industrial product? The research goal was determined to reveal the sensory stimulus and its role in designing the contemporary industrial product. The research also included the keywords (sensory stimulus, understanding and interpretation). The theoretical framework included two topics, the first was entitled Sensory Stimulus and its Role in Understanding and Interpreting the Contemporary Industrial Product, while the second topic was entitled Sensory Stimulus and its Role in Understanding and Interpreting the Contemporary Industrial Product. The research reached the following results, the most important of which are: - The sensory stimulus represents a fundamental presence in the design of the contemporary industrial product, and it often places the recipient or user in a picture of cognitive balance with the contemporary industrial product. The most important conclusions of which are (the interconnection of understanding and interpretation came through the associative relationship between them through the sensory stimulus in the industrial product at a rate of 80%). The research also reached a set of recommendations and suggestions